Birth order and fund manager's trading behavior: Role of sibling rivalry - Vikas Agarwal; Alexander Elmar Cochardt; Vitaly Orlov (University of Cologne, Centre for Financial Research (CFR), 2022)
This paper investigates the role of birth order on managerial behavior using rich data on familial background of US mutual fund managers. We find that managers who are born later in the sibling hierarchy take on more investment risks relative to first-born managers, but perform worse. Motivated by sensation seeking, later-born managers take extreme style bets, hold more lottery stocks, and report more civil and regulatory violations compared to lower-birth-order managers. Taken together, our findings suggest that birth order-induced sensation seeking tendencies originate from sibling rivalry for limited parental resources during childhood, shape trading behavior, and extend beyond portfolio management.
Keywords: G11; G23; 330; birth order; mutual fund manager; sensation seeking; sibling rivalry